2016
DOI: 10.1007/s10910-016-0699-3
|View full text |Cite
|
Sign up to set email alerts
|

On two different kinds of resonances in one-dimensional quantum-mechanical models

Abstract: We apply the Riccati-Padé method and the Rayleigh-Ritz method with complex rotation to the study of the resonances of a one-dimensional well with two barriers. The model exhibits two different kinds of resonances and we calculate them by means of both approaches. While the Rayleigh-Ritz method reveals each set at a particular interval of rotation angles the Riccati Padé method yields both of them as roots of the same Hankel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…This pole can be moved through any ray in the complex plane, and for this reason the solutions of equation ( 17) yield approximations to the eigenvalues of equation ( 14) whose corresponding eigenfunctions decay asymptotically through different rays in the complex plane. Concordantly, the roots of equation ( 17) persist if a complex rotation of the variable is performed [36]. Another important characteristic of the RPM is that H D d typically exhibits a great number of roots in the neighborhood of each eigenvalue; this makes it easier to differentiate the roots that approximate an eigenvalue from those that are spurious, but it also complicates the task to find the optimal sequence of roots that converges to each eigenvalue by means of iterative methods.…”
Section: Riccati-padé Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This pole can be moved through any ray in the complex plane, and for this reason the solutions of equation ( 17) yield approximations to the eigenvalues of equation ( 14) whose corresponding eigenfunctions decay asymptotically through different rays in the complex plane. Concordantly, the roots of equation ( 17) persist if a complex rotation of the variable is performed [36]. Another important characteristic of the RPM is that H D d typically exhibits a great number of roots in the neighborhood of each eigenvalue; this makes it easier to differentiate the roots that approximate an eigenvalue from those that are spurious, but it also complicates the task to find the optimal sequence of roots that converges to each eigenvalue by means of iterative methods.…”
Section: Riccati-padé Methodsmentioning
confidence: 99%
“…It was originally proposed for the computation of bound states, but later it was found that it is also able to yield resonances without resorting explicitly to a complex rotation [27,28]. Its ensuing applications showed that it is able to compute them very accurately and with comparatively little cost [31][32][33][34][35][36][37]. For example, the resonances for the Stark effect in the hydrogen atom computed by us in [37] are to our knowledge the most accurate available in literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RPM has been thoroughly described in previous works [33][34][35][36][37][38][39][41][42][43][44], but for the sake of completeness we briefly recall its main features here. We also revisit the main generalities of the Schrödinger equation for H + 2 , and detail the application of the RPM to solve it.…”
Section: The Methodsmentioning
confidence: 99%